A lightning‐based search for nearby observationally dim terrestrial gamma ray flashes. Issue 23 (11th December 2015) - McTague, L. E.; Cummer, S. A.; Briggs, M. S.; Connaughton, V.; Stanbro, M.; Fitzpatrick, G.
Abstract: Current space‐based observations of terrestrial gamma ray flashes (TGFs) are capable of identifying only TGFs that exceed a lower brightness threshold. Observationally, dim TGFs that fall below this threshold are consequently difficult to find using photon‐only search algorithms. Such TGFs are a potentially important part of the overall global TGF rate, and information on their occurrence rate would give important insight into TGF generation mechanisms. We describe and implement a lightning‐based search for TGFs that uses the location and time of National Lightning Detection Network reported positive polarity, in‐cloud (+IC) discharges of the type known to be directly associated with TGFs. These events identify a 200 μs search window when any associated TGF photons would have been detected. We show that this approach can detect TGFs without requiring a lower threshold on the detected photon brightness of the event, and thus is capable, in principle, of finding a population of weak TGFs. We find that TGFs occur at a rate between 1 in 40 and 1 in 500 of in‐cloud lightning events that meet our study's criteria. The distribution of gamma ray counts in the search windows exhibits a statistically significant lack of nearby dim TGFs below the GBM search threshold. The data favor a brightness distribution in which nearby observationally dim TGFs are rare. Key Points: We developed a method to identify TGFs with no lower limit on fluence The fraction of strong in‐cloud lightning that produces TGFs is estimated to be around 1 in 100 Dim TGFs are likely rarer than expected from extrapolation of the known rate of brighter TGFs